Floral vasculature and its variation for carpellary supply in Anthurium (Araceae, Alismatales) - Poli, Letícia P. [UNESP]; Temponi, Lívia G.; Coan, Alessandra I. [UNESP] (PeerJ, 2017)
Introduction and Aims. Anthurium is the largest genus of Araceae, with 950 species distributed in the neotropics. Despite the great diversity of the genus, the knowledge of its floral vasculature is based on observations in only two species, viz. A. denudatum and A. lhotzkyanum, with remarkable variation in vascular carpellary supply: carpels are either vascularized by ventral bundles alone or by reduced dorsal bundles in addition to the ventral ones. Our main objective is to test this peculiar variation through a detailed anatomical study of the floral vasculature in taxa belonging to some sections of Anthurium designated as monophyletic groups in recent phylogenies. Methods. We compare the floral vasculature of 20 neotropical species belonging to distinct sections of Anthurium, using both light and confocal laser scanning microscopies. Results. The number and position of vascular bundles are constant within the tepals and stamens, regardless of the species and sections studied. However, the gynoecium vasculature exhibits variation between species belonging to the same or different sections. Our results reveal two patterns of vasculature: carpels vascularized by synlateral bundles alone (Pattern A) and carpels vascularized by both dorsal and synlateral bundles (Pattern B). Pattern A is shared by the majority of species studied here and corroborates the previous data in the literature. Pattern B occurs in three species: A. affine (Anthurium sect. Pachyneurium series Pachyneurium), A. obtusum and A. scandens (Anthurium sect. Tetraspermium), described here for the first time for the genus. Conclusions. The variation in the supply to the carpels in Anthurium is corroborated here. However, our results in addition to those from the available literature suggest the existence of three patterns (A, B and C) of carpellary vasculature. Based on the recent phylogeny of Anthurium it is possible to notice that the three patterns of carpellary vasculature occur in representatives of Clade B and deserve to be investigated in a larger number of species. Pattern A could be a plesiomorphy for the genus and the occurrence of dorsal bundles could be a derived character. Our data contributes to the taxonomy and to the understanding of the floral evolution of the largest neotropical genus of Araceae.
Keywords: Carpel; Dorsal bundle; Monocotyledons; Synlateral bundle; Vascular complex